Decoupage Art in the Modern Egyptian Painting - Mohamed, Enas Dahi Ahmed (Dirasat: Human and Social Sciences, 2023)
Objectives: This research aims to trace the history and techniques of decoupage art as a medium in contemporary Egyptian painting. It explores how decoupage enhances tactile values and achieves visual richness in artworks. Additionally, it examines the tactile qualities of decoupage in Egyptian pictorial works through descriptive analysis of selected pieces by contemporary artists. The hypothesis suggests that the use of decoupage art enriches visual and tactile experiences in contemporary Egyptian figurative painting. The significance of this study lies in shedding light on a novel approach that enhances the surface texture of contemporary Egyptian painting, specifically the decoupage technique. It also explores diverse technical approaches through artistic experimentation. Methods: The researcher adopts a historical approach to examine the emergence of decoupage art and utilizes a descriptive and analytical approach to study samples of contemporary Egyptian artists’ works that incorporate decoupage techniques. Results: The research confirms the hypothesis that the use of decoupage in contemporary Egyptian artworks enhances visual richness and artistic value. The technique achieves color and linear diversity through the decorative elements of the decoupage paper. Conclusions: Based on these findings, the researcher presents recommendations and proposals. These include encouraging experimentation with various materials and interdisciplinary approaches to enrich contemporary artistic work. It advocates for the development of an educational curriculum that allows art students to enhance their visual and aesthetic experiences. Furthermore, it emphasizes the importance for artists to pay attention to the materials available in their local environment and utilize their aesthetic components to the fullest extent.